Religion In The Construction Of Mass Media; A Study On The Kompas And Republika Framing Of The Terrorism News - Zakiah Zakiah (Balai Penelitian dan Pengembangan Agama Semarang, 2015)
This article concerns on how Kompas and Republika framed terrorism news and how they construct a religion (Islam) in those terrorism news. The way of the media exposing and selecting the facts to be published in their newspaper is an important aspect to be studied. This is because each media has its own inclination. Data was gathered using library research. Then, those collected data were analyzed using framing analysis and constructivism perspective. The results show that Kompas and Republika clearly said that Islam has nothing to do with terrorism and the terrorists have relationship with the International radical group like JI and Al-Qaeda. On the other hand, both newspapers have a slight difference in exposing the relationship between terrorists and pesantren. Republika said that those terrorists were not connected with pesantren. Meanwhile Kompas exposed the pro and contra about this matter. In addition, both media have trivial differences in reporting about dakwah prohibition.